Morc4 is a novel functional gene associated with lipid metabolism in BXD recombinant inbred population - Yang, Zhanyi; Xu, Jiaai; Yang, Xiaoyu; Yi, Pengcheng; Ruan, Jian; Wu, Yingying; Li, Yushan; Tian, Geng; Xu, Fuyi; Mi, Jia; Li, He; Yang, Chunhua (Frontiers in Cardiovascular Medicine, 2025)
AimThe dysregulation of hepatic lipid metabolism is closely associated with dyslipidemia. Previous research suggested that Hepatic Morc4 may play a role in regulating lipid metabolism. This research aims to elucidate the function of MORC4 in hepatic lipid metabolism, thereby improving the understanding of the molecular mechanisms underlying lipid metabolism disorders.MethodsData regarding circulating lipid traits and hepatic Morc4 expression in BXD mice were obtained from GeneNetwork. An Expression-Based Phenome-wide Association Study (ePheWAS), correlation analysis, and gene enrichment analysis were conducted to explore the relationship between Morc4 expression and hepatic lipid metabolism. in vitro, the levels of total cholesterol (TC) and triglycerides (TG), lipid accumulation, and the expression of lipid metabolism-related genes were assessed subsequent to MORC4 knockdown/overexpression in hepatocytes. in vivo, the impact of Morc4 knockout on lipid metabolism-related traits in mice was examined using the IMPC database.ResultsHepatic Morc4 level was found to be negatively correlated with plasma free fatty acids and triglycerides in BXD mice. Further analysis indicated that genes associated with Morc4 were enriched in the cholesterol metabolic pathway. In hepatocytes, MORC4 knockdown significantly elevated total TC/TG levels, as well as enhanced lipid accumulation. Whereas MORC4 overexpression restored total TC/TG levels, along with lipid accumulation in knockdown cell lines. Furthermore, MORC4 knockdown led to an increased expression of genes associated with cholesterol synthesis (HMGCR), varying levels of genes implicated in the uptake of fatty acids and cholesterol (PCSK9, PLTP, CD36), and a decrease in the levels of genes involved in triglyceride hydrolysis (APOC2, APOA4, LIPG, LIPA). MORC4 overexpression reversed the observed alterations in the expression levels of these genes. According on the IMPC database, Morc4 knockout in mice resulted in increased fat mass, fat/body weight ratio, and elevated cholesterol level and ratio.ConclusionThis study identifies MORC4 as a crucial regulator of hepatic lipid metabolism and underscores its potential as a therapeutic target for disorders related to lipid.